1996
DOI: 10.1073/pnas.93.11.5329
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of muscle glycogen synthesis in insulin-resistant offspring of parents with non-insulin-dependent diabetes mellitus immediately after glycogen-depleting exercise.

Abstract: To examine the impact of insulin resistance on the insulin-dependent and insulin-independent portions of muscle glycogen synthesis during recovery from exercise, we studied eight young, lean, normoglycemic insulin-resistant (IR) offspring of individuals with non-insulin-dependent diabetes mellitus and eight age-weight matched control (CON) subjects after plantar flexion exercise that lowered muscle glycogen to -25% of resting concentration. After '20 min of exercise, intramuscular glucose 6-phosphate and glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 27 publications
8
96
2
1
Order By: Relevance
“…Since the initial intense glycogen-depleting exercise study demonstrated that in normal healthy human subjects there was an early phase of rapid glycogen resynthesis (12-30 mmol/l per h) lasting approximately 45 min that was insulin independent and a subsequent period of glycogen resynthesis (above approximately 35 mmol glycogen/l) that was much slower (approximately 3 mmol/l per h) and insulin dependent (Price et al 1994a), a second exercise study compared control subjects with the insulin-resistant offspring of parents with non-insulin-dependent diabetes mellitus (NIDDM; Price et al 1996). During the insulinindependent portion of recovery from glycogen-depleting exercise the glycogen recovery rates were not significantly different between the control and the insulin-resistant groups (Fig.…”
Section: Exercise Studies Of Muscle Metabolismmentioning
confidence: 99%
“…Since the initial intense glycogen-depleting exercise study demonstrated that in normal healthy human subjects there was an early phase of rapid glycogen resynthesis (12-30 mmol/l per h) lasting approximately 45 min that was insulin independent and a subsequent period of glycogen resynthesis (above approximately 35 mmol glycogen/l) that was much slower (approximately 3 mmol/l per h) and insulin dependent (Price et al 1994a), a second exercise study compared control subjects with the insulin-resistant offspring of parents with non-insulin-dependent diabetes mellitus (NIDDM; Price et al 1996). During the insulinindependent portion of recovery from glycogen-depleting exercise the glycogen recovery rates were not significantly different between the control and the insulin-resistant groups (Fig.…”
Section: Exercise Studies Of Muscle Metabolismmentioning
confidence: 99%
“…Defective insulinstimulated glucose uptake in muscle is associated with impaired muscle membrane glucose transport [2,3] and reduced muscle glycogen synthase activity [2,[4][5][6][7], which in turn may both result from impaired insulin signalling.…”
Section: Introductionmentioning
confidence: 99%
“…These effects might be related to increased numbers of mitochondria and the GLUT4 isoform of the glucose transporter in skeletal muscles, respectively. GLUT4, the insulin-responsive glucose transporter, is expressed in skeletal muscles, heart, and adipose tissues, and the number of GLUT4 on plasma membrane becomes a rate-limiting step for whole-body glucose clearance under physiological conditions (3)(4)(5). Thus, exercise training modifies the skeletal muscle to metabolize more fatty acids and glucose.…”
mentioning
confidence: 99%